What Is Renewable Energy? - Faxri Hamitov (Genius Journals, 2022)
The article talks about types of renewable energy and their impact on nature. In general, renewable energies are one of the most normal and promising ways to save our limited resources and meet the needs of humanity in the future.
Keywords: energy; sun; renewable; regenerative